Emerging technologies for the evaluation of spatio-temporal polymerisation changes in flowable vs. sculptable dental resin-based composites - Marovic, Danijela; Haugen, Håvard J.; Par, Matej; Linskens, Stefanie; Mensikova, Emile; Negovetic, Mandic Visnja; Leeuwenburgh, Sander; Nogueira, Liebert P.; Vallittu, Pekka K.; Ma, Qianli (Elsevier BV, 2025)
Background: This study presents a novel multi-technique approach that integrates micro-CT and optical photothermal infrared spectroscopy (O-PTIR) to evaluate polymerisation differences, so-called spatio-temporal polymerisation properties, between flowable and sculptable dental resin-based composites.
Methods: Ten commercially available dental composites were investigated, including flowable and sculptable counterparts from the same manufacturer. Eight parameters were evaluated: short-term polymerisation characteristics (degree of conversion after 5 min, maximum polymerisation rate, time to reach maximum polymerisation rate) was measured using ATR-FTIR with real-time monitoring; changes in the degree of conversion with depth were evaluated with O-PTIR, 3D visualisation of shrinkage patterns, overall volumetric shrinkage, depth-specific shrinkage, and porosity were measured using micro-CT; surface morphology with detailed measurements of elemental composition was characterised using SEM/EDX; light transmittance was analysed with a NIST-referenced spectrometer.
Results: The study found that the increase in filler weight and volume ratio reduced the degree of conversion and polymerisation shrinkage, while moderately influencing the maximum polymerisation rates. The time to reach maximum polymerisation rates and light transmittance were not dependent on the filler amount. O-PTIR assessed a depth-dependent decrease in the degree of conversion for both composite types, with flowable composites generally showing a greater decrease in the degree of conversion than sculptable composites, except for bulk-fill composites. Micro-CT scans showed significantly higher flowable shrinkage values than their sculptable counterparts, highlighting the performance differences between the two types of composites.
Conclusions: The findings of this study have practical implications for the selection and use of dental composites. Flowable composites, despite their higher degrees of conversion and polymerisation rates, also exhibit higher volumetric shrinkage, which can be detrimental for clinical applications. The new measurement methods used in this study provide a comprehensive overview of the polymerisation behaviour of commercially available dental composites, offering valuable insights for material optimisation.